Permasalahan dalam Penyelenggaraan Pendidikan Inklusi di SDN Pinang 7 - Nurfadhillah, Septy; Setyorini, Aprilia; Cempaka, Bunga; Azhar, Cantika Rofiqoh; Fauziah, Putri; Jamirullah, Raihan Fadhlurrahman; Ramadhanty, Salma; Kusminarti, Shanti (Lembaga Yasin AlSys, 2022)
The implementation of inclusive education in Indonesia aims to provide educational facilities and services for children with special needs (ABK). The implementation of inclusive education has been implemented in elementary schools throughout Indonesia, especially big cities, but in its implementation found many problems. This study aims to describe the problems in the implementation of inclusive education at SDN Pinang 7. Special (GPK) SDN Pinang 7 Tangerang City. The method used is descriptive qualitative which aims to describe